A randomized placebo controlled trial to evaluate the effects of butamirate and dextromethorphan on capsaicin induced cough in healthy volunteers. (December 2014) - Faruqi, Shoaib; Wright, Caroline; Thompson, Rachel; Morice, Alyn H.
<x xml:space="preserve">Abstract</x> Aims The examination of cough reflex sensitivity through inhalational challenge can be utilized to demonstrate pharmacological end points. Here we compare the effect of butamirate, dextromethorphan and placebo on capsaicin‐induced cough in healthy volunteers. Methods In this randomized, placebo‐controlled, six way crossover study the effect of dextromethrophan 30 mg, four doses of butamirate and placebo was evaluated on incremental capsaicin challenges performed at baseline and 2, 4, 6, 8, 12 and 24 h following dosing. The primary end point was the area under the curve (AUC(0, 12h)) of log10C5 from pre‐dose to 12 h after dosing. Plasma butamirate metabolites were analyzed to evaluate pharmacokinetic and pharmacodynamic relationships. Results Thirty‐four subjects (13 males, median age 25 years) completed the study. Cough sensitivity decreased from baseline in all arms of the study. Dextromethorphan was superior to placebo (P = 0.01) but butamirate failed to show significant activity with maximum attenuation at the 45 mg dose. There was no apparent relationship between pharmacokinetic and pharmacodynamic parameters for butamirate. Conclusions We have demonstrated for the first time that dextromethorphan attenuates capsaicin challenge confirming its broad activity on the cough reflex. The lack of efficacy of butamirate could be due to formulation issues at higher doses.